Heritability and sources of Ascochyta blight resistance in common bean - Hanson, PM; Pastor Corrales, Marcial A.; Kornegay, Julia L. (Scientific Societies, 1993)
Common bean germ plasm (Phaseolus vulgaris) with intermediate Ascochyta blight (caused by Phoma exigua var. diversispora) resistance has been identified at CIAT. The heritability and inheritance of resistance to this pathogen were studied in three resistant climbing bean sources. Narrow-sense heritability estimates determined by the regression of the F2-derived F4 line means on F2-derived F3 line means from crosses Carioca (S) × G 10817 (R) and G 10088 (S) × G 10747 (R) were low to moderate (0.19–0.64), depending on the cross and character measured. A generation means analysis of resistant parents G 10817 and G 10823 crossed with the susceptible parent G 12488 indicated that additive, dominance, and epistatic effects were important in the inheritance of resistance. Evaluation of lines for resistance should be conducted in advanced generations in replicated trials.